SEMI AUTO WORK AIDS (JIG) MANUFACTURING TO IMPROVE THE CONSISTENCY OF CRIMPING CABLE PRODUCT QUALITY - Jantri Wadi; Budhi M. Suyitno; Susanto Sudiro (Teknobiz : Jurnal Ilmiah Program Studi Magister Teknik Mesin, 2026)
A work aid (jig) to speed up the cable crimping process without reducing quality and minimizing reject cables during the process. This cable crimping work aid (jig) provides ease and comfort for the user/operator to improve the consistency of the quality of cable crimping products and reduce or suppress the degree of defects in terminal and cable bonds. In the manufacture of this cable crimping work aid, a Pneumatic Cylinder is used. The motion system has optimization or effectiveness when used within certain limits. The size limits that can lead to optimal use of pneumatics include: piston diameter between 6 - 320 mm, stroke length 1-2000 mm, power required 2-15 bar. Meanwhile, to speed up the assembly/design process, using Failure Mode and Effects Analysis (FMEA) analysis, as well as using the Bill of Materials (BOM) method as part of the design process to determine items to be purchased or produced. Below is a description of what is made in the assembly process of the cable crimping work aid.